Performance Analysis of Different Polymer Core for Badminton String Application - Sanusi, Shahmir Hayyan; Nor Azman, Afiq (Research Progress in Mechanical and Manufacturing Engineering, 2021)
The string of a badminton racket is one of the main components that affect the performance of a player because the performance of the string could affect the accuracy and power of a stroke during a match. Nowadays there are many strings that are made from variety type of material in the market. As technology evolves, polymers are used manufacturing synthetics strings. Polymers are used because they have a wide range of properties and many type of the polymer are extremely tough or stiff. Polymer can be relatively cheap to process and it is lightweight. This study will help to highlight and compare which polymer material that will give the best performance if it is made into a badminton string. The polymers that are being compared in this study is polyester, nylon, polyethylene and polyphtalamide. The finite element model is created and simulated by using a software called ABAQUS. Two finite element simulation were carried out in this study, which is drop test simulation and tensile test simulation. The first test is done to determine the value of coefficient of restitution (COR) of each material and the dwell time of the string during an impact between the ball and the string-bed. The second test is to determine the stress vs strain graph of each string of different polymer. From the results of these simulation, the badminton string performance of different material can be compared in terms of COR value, dwell time and stress vs strain graph and the best material for a badminton string core will be determined.